O KOMUNIKACYJNYCH I MEDIACYJNYCH KOMPETENCJACH EGZAMINATORA NA EGZAMINIE USTNYM Z JĘZYKA OBCEGO (NA PRZYKŁADZIE EGZAMINU CERTYFIKACYJNEGO UW Z JĘZYKA FRANCUSKIEGO) - Kucharczyk, Radosław; Sujecka-Zając, Jolanta (Neofilolog, 2019)
The purpose of this article is to reflect on the examiner’s mediation skills in the process of certifying speaking ability in a foreign language. In the theoretical part we discuss the principles of language proficiency certification in accordance with the guidelines of the Council of Europe and the specificity of certifying speaking ability. Then we present the results of our own research the aim of which was to evaluate the examiners’ mediation skills during the French oral examination at level B2 at the University of Warsaw.